Gait‐Related Metabolic Covariance Networks at Rest in Parkinson's Disease. Issue 6 (14th March 2022) - Sigurdsson, Hilmar P.; Yarnall, Alison J.; Galna, Brook; Lord, Sue; Alcock, Lisa; Lawson, Rachael A.; Colloby, Sean J.; Firbank, Michael J.; Taylor, John‐Paul; Pavese, Nicola; Brooks, David J.; O'Brien, John T.; et al.
Abstract: Background: Gait impairments are characteristic motor manifestations and significant predictors of poor quality of life in Parkinson's disease (PD). Neuroimaging biomarkers for gait impairments in PD could facilitate effective interventions to improve these symptoms and are highly warranted. Objective: The aim of this study was to identify neural networks of discrete gait impairments in PD. Methods: Fifty‐five participants with early‐stage PD and 20 age‐matched healthy volunteers underwent quantitative gait assessment deriving 12 discrete spatiotemporal gait characteristics and [ 18 F]‐2‐fluoro‐2‐deoxyglucose‐positron emission tomography measuring resting cerebral glucose metabolism. A multivariate spatial covariance approach was used to identify metabolic brain networks that were related to discrete gait characteristics in PD. Results: In PD, we identified two metabolic gait‐related covariance networks. The first correlated with mean step velocity and mean step length ( pace gait network ), which involved relatively increased and decreased metabolism in frontal cortices, including the dorsolateral prefrontal and orbital frontal, insula, supplementary motor area, ventrolateral thalamus, cerebellum, and cuneus. The second correlated with swing time variability and step time variability ( temporal variability gait network ), which included relatively increased and decreased metabolism in sensorimotor, superior parietal cortex, basal ganglia, insula, hippocampus, red nucleus, and mediodorsal thalamus. Expression of both networks was significantly elevated in participants with PD relative to healthy volunteers and were not related to levodopa dosage or motor severity. Conclusions: We have identified two novel gait‐related brain networks of altered glucose metabolism at rest. These gait networks could serve as a potential neuroimaging biomarker of gait impairments in PD and facilitate development of therapeutic strategies for these disabling symptoms. © 2022 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society